2017
DOI: 10.1111/exd.13331
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies of non‐inflammatory bullous pemphigoid hardly deplete type XVII collagen of keratinocytes

Abstract: Type XVII collagen (COL17) and the non-collagenous 16A (NC16A) domain is regarded as the major pathogenic domains for bullous pemphigoid (BP). Some patients with BP have autoantibodies against parts of COL17 outside the NC16A domain (hereinafter the non-NC16A domain) and show less inflammatory manifestations. There were no significant differences in titres and IgG subclasses between NC16A-BP and non-NC16A-BP as determined by indirect immunofluorescent microscopy. The neutrophil activation capacities determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Previous reports demonstrated that BP180 C‐term‐IgG does not show pathogenicity in vivo nor in vitro . We next studied the effects of Fc‐binding proteins on mAb C17‐C1 targeting the C‐terminus of BP180.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports demonstrated that BP180 C‐term‐IgG does not show pathogenicity in vivo nor in vitro . We next studied the effects of Fc‐binding proteins on mAb C17‐C1 targeting the C‐terminus of BP180.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of COL17 in the TritonX‐100‐soluble fraction (ie non‐hemidesmosomal COL17) was found to be decreased at 6 hours after BP‐IgG stimulation, and that in the TritonX‐100‐insoluble fraction (ie hemidesmosomal COL17) was found to be decreased at 48 hours. COL17 depletion was observed in the setting of stimulation with anti‐NC16A BP‐IgG, but not with non‐NC16A BP‐IgG (Figure B, right).…”
Section: Evidence Of Non‐complement Relevancementioning
confidence: 96%
“…Studies showing that antibodies targeting areas outside of NC16A had less capacity to deplete COL17 on keratinocytes than antibodies targeting NC16A suggest that the pathogenicity of autoantibodies in BP could be epitope dependent 61, 62 . Recent studies have offered some biomarkers for more efficient diagnosis and prediction of prognosis in pemphigoid 63, 64 .…”
Section: Pemphigoidmentioning
confidence: 99%